Deserved : economic memories after the fall of the Iron Curtain - Hilmar, Till 1985- (Columbia University Press, 2023)
After the fall of the Iron Curtain, people across the former socialist world saw their lives transformed. In just a few years, labor markets were completely disrupted, and the meanings attached to work were drastically altered. How did people who found themselves living under state socialism one day and capitalist democracy the next adjust to the changing social order and its new system of values? Till Hilmar examines memories of the postsocialist transition in East Germany and the Czech Republic to offer new insights into the power of narratives about economic change. Despite the structural nature of economic shifts, people often interpret life outcomes in individual terms. Many are deeply attached to the belief that success and failure must be deserved. Emphasizing individual effort, responsibility, and character, they pass moral judgments based on a person’s fortunes in the job market. Hilmar argues that such frameworks represent ways of making sense of the profound economic and social dislocations after 1989. People craft narratives of deservingness about themselves and others to solve the problem of belonging in a new social order. Drawing on in-depth interviews with engineers and care workers as well as historical and comparative analysis of the breakdown of communism in Eastern Europe, Deserved sheds new light on the moral imagination of capitalism and the experience of economic change. This book also offers crucial perspective on present-day politics, showing how notions of deservingness and moral worth have propelled right-wing populism.